(3GdEYdGe HCYdGe HjJ GGddg GdMQGes - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeSLO GdMQGe GefG heKGHI ddfGS s
(3BNQgG (B:s
(3heGgH GdfSje Ydi GdYTGb HGdWjH hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B17s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B382 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B515 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B36 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs